Hydraulic fracture propagation characteristics of directional perforation fracturing in horizontal wells for deep coalbed methane - Shuxin HUANG; Song LI; Bo CHEN (Shiyou shiyan dizhi)
Deep coalbed methane resources exhibit favorable geological characteristics and significant exploration and development potential, offering a substantial foundation for China's strategy to enhance natural gas storage and production. Directional perforation fracturing of horizontal wells is widely used as an important permeability enhancement technology for deep coalbed methane exploration. However, the mechanisms of hydraulic fracture initiation and propagation under the influence of geological and engineering factors remain unclear. To explore directional perforation fracturing characteristics in deep coal seams, a three-dimensional discrete lattice simulation algorithm was used to establish a numerical model. The paper studied the effects of geological and perforation parameters on fracturing difficulty, fracture morphology, and stimulated reservoir area (SRA). The results showed that, with the increase in elastic modulus, coal seam fracture pressure rose, and SRA and its variation coefficient increased gradually, which is conducive to long and narrow fracture formation. An increase in horizontal stress differences weakened the interaction between hydraulic fractures, reducing SRA while increasing its variation coefficient and fracture aperture. In addition, increasing perforation depth and diameter significantly reduced the fracture pressure in deep coal seams. Higher perforation depths greatly increased SRA, whereas larger perforation diameters decreased SRA, and its variation coefficient increased gradually. Perforation density had no significant impact on fracture pressure, but was positively correlated with SRA. The study suggests that for fracturing of structurally intact coal seams, increasing perforation depth and density while reducing perforation diameter can achieve better results.